Virtual International Exchange: Access, Outcomes, and Programmatic Concerns - Whatley, Melissa; Woodman, Taylor; Glass, Chris (Journal of International Students, 2022)
This editorial provides context for the articles that appear in this special issue and brings them together thematically. We first examine how special issue authors chose to define the term ‘virtual exchange’ in their work and then explore key take-aways from each article in three thematic groups: access; outcomes; and programmatic concerns. Together, the articles in this special issue speak to key issues in virtual international exchange that will be important for researchers and practitioners alike to contend with as the field develops.